2020
DOI: 10.1038/s41541-020-0169-6
|View full text |Cite|
|
Sign up to set email alerts
|

BCG and BCGΔBCG1419c protect type 2 diabetic mice against tuberculosis via different participation of T and B lymphocytes, dendritic cells and pro-inflammatory cytokines

Abstract: Comorbidity between Tuberculosis (TB) and type 2 diabetes (T2D) is one of the greatest contributors to the spread of Mycobacterium tuberculosis (M. tuberculosis) in low-and middle-income countries. T2D compromises key steps of immune responses against M. tuberculosis and it might affect the protection afforded by vaccine candidates against TB. We compared the protection and immune response afforded by the BCGΔBCG1419c vaccine candidate versus that of wild-type BCG in mice with T2D. Vaccination with both BCGΔBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Also, in spleens of BALB/c mice, BCGΔBCG1419c increased T CD3 + CD4 + IFNγ + and T CD3 + CD8 + IFNγ + cells with respect to parental BCG 13 . Moreover, we have observed that BCGΔBCG1419c promote a differential presence in lungs of IFNγ-producing T cells, and activated macrophages in a BALB/c model of active and chronic TB 13 while it changed the relative presence in lungs of B, CD8 + , and dendritic cells, in a BALB/c model of TB-type 2 diabetes 17 . All these findings show that BCG and BCGΔBCG1419c affect the relative composition of adaptive immune cells pre- and post-infection in diverse organs and tissues of vaccinated hosts.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Also, in spleens of BALB/c mice, BCGΔBCG1419c increased T CD3 + CD4 + IFNγ + and T CD3 + CD8 + IFNγ + cells with respect to parental BCG 13 . Moreover, we have observed that BCGΔBCG1419c promote a differential presence in lungs of IFNγ-producing T cells, and activated macrophages in a BALB/c model of active and chronic TB 13 while it changed the relative presence in lungs of B, CD8 + , and dendritic cells, in a BALB/c model of TB-type 2 diabetes 17 . All these findings show that BCG and BCGΔBCG1419c affect the relative composition of adaptive immune cells pre- and post-infection in diverse organs and tissues of vaccinated hosts.…”
Section: Introductionmentioning
confidence: 84%
“…Recently, the vaccine candidate BCGΔBCG1419c was demonstrated to confer equal and/or better protection against experimental TB compared to its parental strain, BCG Pasteur, in a variety of mouse models (BALB/c 13 , 14 , C57BL/6 15 , 16 , and B6D2F1 [C57BL/6J × DBA/2J] 13 ), including a type 2 diabetic BALB/c model 17 , while in guinea pigs it was more effective than BCG in reducing hematogenous spread at 2 months post-infection 18 . The M. bovis BCG1419c gene encodes a phosphodiesterase activity that hydrolyzes bis-(3′-5′)-cyclic dimeric GMP (c-di-GMP), a molecule which reduces bacterial motility and increases biofilm formation (biofilms are sessile bacteria encased within a matrix of an extracellular polymeric substance) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, in spleens of BALB/c mice, BCGDBCG1419c increased T CD3 + CD4 + IFNg + and T CD3 + CD8 + IFNg + cells with respect to parental BCG 13 . Moreover, we have observed that BCGDBCG1419c promote a differential presence in lungs of IFNg-producing T cells, and activated macrophages in a BALB/c model of active and chronic TB 13 while it changed the relative presence in lungs of B, CD8 + , and dendritic cells, in a BALB/c model of TB-type 2 diabetes 17 . All these ndings show that BCG and BCGDBCG1419c affect the relative composition of adaptive immune cells pre-and post-infection in diverse organs and tissues of vaccinated hosts.…”
Section: Introductionmentioning
confidence: 83%
“…Recently, the vaccine candidate BCGDBCG1419c was demonstrated to confer equal and/or better protection against experimental TB compared to its parental strain, BCG Pasteur, in a variety of mouse models (BALB/c 13,14 , C57BL/6 15,16 , and B6D2F1 [C57BL/6J × DBA/2J] 13 ), including a type 2 diabetic BALB/c model 17 , while in guinea pigs it was more effective than BCG in reducing hematogenous spread at 2 months post-infection 18 . The M. bovis BCG1419c gene encodes a phosphodiesterase activity that hydrolyzes bis-(3′-5′)-cyclic dimeric GMP (c-di-GMP), a molecule which reduces bacterial motility and increases bio lm formation (bio lms are sessile bacteria encased within a matrix of an extracellular polymeric substance) 19 .…”
Section: Introductionmentioning
confidence: 99%
“…To induce T2D, we used a non-genetic mouse model of diet-induced insulin resistance and pancreatic beta cell insufficiency, as previously reported (24,25). Briefly, male BALB/c 3-week-old mice were fed with a high-fat diet (HFD) containing 45% of calories from fat during the whole course of the experiment.…”
Section: Experimental Model Of T2d and Progressive Pulmonary Tb In Balb/c Micementioning
confidence: 99%